EMPOWERMENT OF COFFEE FARMING GROUPS IN BENER MERIAH - Ti Aisyah; Risna Dewi; Muhammad Hasyem; Mauludi; Risma Junita; Teuku Alfiady (FISIP Universitas Malikussaleh, 2026)
Article reviews the Empowerment of Coffee Farmer Groups in Sedie Jadi Village, Bukit District, Bener Meriah Regency. The purpose of this study is to determine how the empowerment of coffee farmer groups in Sedie Jadi Village and also to determine the obstacles in empowering coffee farmer groups in Sedie Jadi Village. This study uses a qualitative descriptive research method with data collection methods through observation, interviews and documentation. Data analysis techniques used in this study are data reduction, data presentation and conclusion drawing. Based on the general results of the study, it shows that in general the empowerment activities of coffee farmer groups in Sedie Jadi Village, Bukit District, Bener Meriah Regency have been empowered in three stages, at the stage that is possible by providing counseling and dampening as well as basic capabilities possessed by farmer groups, at the empowerment stage carried out by providing training and assistance, at the protection stage it was found that coffee farmer groups are independent because they are able to carry out their activities without dampening from any party, building group cooperation and forming deliberation forums. The obstacles found by researchers indicate that coffee farmer groups in Sedie Jadi Village rarely receive direct counseling from PPL, coffee farmer groups have difficulty in applying for assistance and also difficulty in obtaining subsidized fertilizer. Empowerment of coffee farmer groups in Sedie Jadi Village, Bukit District, Bener Meriah Regency can be seen based on the Law of the Republic of Indonesia Number 19 of 2013 concerning Protection and Empowerment of Farmers, Regulation of the Minister of Agriculture Number 67 of 2016 concerning Development of Farmer Institutions and Qanun of Aceh Province Number 3 of 2020 Protection and Empowerment of Farmers. This research was conducted based on Kartasasmita's theory which contains 3 stages in community empowerment, namely empowerment, empowerment and protection.